Variable expressivity of KMT2B variants at codon 2565 in patients with dystonia and developmental disorders - Stehr, Antonia M; Fischer, Jan; Mirza-Schreiber, Nazanin; Bernardi, Katerina; Porrmann, Joseph; Harrer, Philip; Kaiser, Frank; Jamra, Rami Abou; Winkelmann, Juliane; Jech, Robert; Koy, Anne; Oexle, Konrad; et al. (Parkinsonism & related disorders, 2025)
INTRODUCTION: Variable expressivity is an emerging characteristic of KMT2B-related dystonia. However, it remains poorly understood whether variants reoccurring at specific sites of lysine-specific methlytransferase-2B (KMT2B) can drive intra- and interfamilial clinical heterogeneity. Our goal was to ascertain independent families with variants affecting residue Arg2565 of KMT2B. METHODS: Whole-exome/genome sequencing, multi-site recruitment, genotype-phenotype correlations, and DNA methylation episignature analysis were performed. RESULTS: We report four individuals from two families harboring the variant c.7693C > G, p.Arg2565Gly. In an additional patient, a de-novo c.7693C > T, p.Arg2565Cys variant was identified. The observed phenotypic spectrum ranged from childhood-onset dystonia (N = 2) over unspecific intellectual disability syndromes (N = 2) to undiagnosed behavioral symptoms in adulthood (N = 1). Samples bearing p.Arg2565Gly had a KMT2B-typical episignature, although the effect on methylation was less pronounced than in carriers of loss-of-function KMT2B variants. CONCLUSIONS: We established the existence of a KMT2B missense-mutation hotspot associated with varying degrees of disease severity and expression, providing information for patient counseling and elucidation of pathomechanisms.
Keywords: Young Adult; Dystonic Disorders; Mutation, Missense; histonlysin-N-methyltransferasa; Male; Pedigree; rodokmen; missense mutace; Histone-Lysine N-Methyltransferase; mladý dospělý; Adolescent; Dystonia; sekvenování exomu; Child; dítě; Adult; dystonické poruchy; dospělí; mužské pohlaví; mladiství; dystonie; lidé; ženské pohlaví; Humans; vývojové poruchy u dětí; Female; Exome Sequencing; lidé středního věku; Middle Aged; Developmental Disabilities